Efektivitas Token Ekonomi dalam Menurunkan Agresifitas pada Remaja - Magfiroh, Norma Hasanatul; Jamaluddin, Muhammad (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2024)
Aggressive behavior is an attitude that is often shown by teenagers. Adolescence is also identified with the inability of adolescents to control their emotions. The purpose of this study was to determine the effectiveness of the token economy to reduce aggressiveness in adolescents. The method used is qualitative-experimental, namely pre-experimental. Data collection was carried out using a behavioral checklist and using an A-B withdrawal design. The research subjects were 13-year-old girls from strict parent families. The results showed that there was a decrease in aggressiveness at an average anger of 3.7 to 0.4. So that the economic token is effective for reducing aggressiveness in adolescents